PELATIHAN PEMBUATAN LAB VIRTUAL FISIKA MENGGUNAKAN SOFTWARE MODELLUS UNTUK GURU SMA/SMK DI KOTA TEGAL DAN SEKITARNYA - Langgeng Asmoro; Muhammad Rifqi Tsani; Frans Tohom (Kanigara, 2023)
The development of technology and information is growing very fast. Learning Physics is a science that refers to natural phenomena. Physics in the delivery of material in class is done by using lectures, demos, and practicum methods in the laboratory. Many physics teachers are not optimal in utilizing technology. In this activity the author tries to contribute to guiding high school teachers in Tegal City in making a simulation-based virtual laboratory using the help of modellus software. In this activity, teachers are expected to understand how to create and develop a simulation-based virtual laboratory with the help of modellus software. Community Service Activities (PKM) are carried out online or distance learning in order to prevent the transmission of COVID-19. In general, participants rated the activity as 5% Fair, 75% Good and 20% Very Good